Multimodal measurement of glycocalyx degradation during coronary artery bypass grafting - Bol, Martine E.; Huckriede, J. B.; van de Pas, K. G. H.; Delhaas, T.; Lorusso, R.; Nicolaes, G. A. F.; Sels, J. E. M.; van de Poll, M. C. G. (Frontiers in Medicine, 2022)
Background Glycocalyx shedding and subsequent endothelial dysfunction occur in many conditions, such as in sepsis, in critical illness, and during major surgery such as in coronary artery bypass grafting (CABG) where it has been shown to associate with organ dysfunction. Hitherto, there is no consensus about the golden standard in measuring glycocalyx properties in humans. The objective of this study was to compare different indices of glycocalyx shedding and dysfunction. To this end, we studied patients undergoing elective CABG surgery, which is a known cause of glycocalyx shedding. Materials and methods Sublingual glycocalyx thickness was measured in 23 patients by: 1) determining the perfused boundary region (PBR)—an inverse measure of glycocalyx thickness—by means of sidestream dark field imaging technique. This is stated double, 2) measuring plasma levels of the glycocalyx shedding products syndecan-1, hyaluronan, and heparan sulfate and 3) measuring plasma markers of impaired glycocalyx function and endothelial activation (Ang-2, Tie-2, E-selectin, and thrombomodulin). Measurements were performed directly after induction, directly after onset of cardiopulmonary bypass (CPB), and directly after cessation of CPB. We assessed changes over time as well as correlations between the various markers. Results The PBR increased from 1.81 ± 0.21 μm after induction of anesthesia to 2.27 ± 0.25 μm (p < 0.0001) directly after CPB was initiated and did not change further during CPB. A similar pattern was seen for syndecan-1, hyaluronan, heparan sulfate, Ang-2, Tie-2, and thrombomodulin. E-selectin levels also increased between induction and the start of CPB and increased further during CPB. The PBR correlated moderately with heparan sulfate, E-selectin, and thrombomodulin and weakly with Syndecan-1, hyaluronan, and Tie-2. Shedding markers syndecan-1 and hyaluronan correlated with all functional markers. Shedding marker heparan sulfate only correlated with Tie-2, thrombomodulin, and E-selectin. Thrombomodulin correlated with all shedding markers. Conclusion Our results show that glycocalyx thinning, illustrated by increased sublingual PBR and increased levels of shedding markers, is paralleled with impaired glycocalyx function and increased endothelial activation in CABG surgery with CPB. As correlations between different markers were limited, no single marker could be identified to represent the glycocalyx in its full complexity.